2022
DOI: 10.3390/ijerph19106348
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Activity Status in the Relationship between Obesity and Carotid Intima-Media Thickness (CIMT) in Urban South African Teachers: The SABPA Study

Abstract: Globally, the prevalence of physical inactivity and obesity are on the rise, which may increase carotid intima-media thickness (CIMT) as a marker of subclinical atherosclerosis. This study assessed the association between physical activity (PA), obesity, and CIMT. A cross-sectional study design was used, including a sub-sample (n = 216) of teachers who participated in the Sympathetic Activity and Ambulatory Blood Pressure in Africans (SAPBA) study. Measurements included the following: physical activity status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Parsons et al found an association between increased SB and worse cIMT, while an inverse relationship was found between LPA and MVPA with cIMT, although MVPA did not have a stronger association than LPA 65. Several studies (n=5) found no relationship between cIMT and PA 20 49 73–75. Other studies ( n =4) found a negative association between cIMT and PA and/or a positive association between cIMT and SB, but not after adjusting for confounders 19 21 76 77.…”
Section: Resultsmentioning
confidence: 97%
“…Parsons et al found an association between increased SB and worse cIMT, while an inverse relationship was found between LPA and MVPA with cIMT, although MVPA did not have a stronger association than LPA 65. Several studies (n=5) found no relationship between cIMT and PA 20 49 73–75. Other studies ( n =4) found a negative association between cIMT and PA and/or a positive association between cIMT and SB, but not after adjusting for confounders 19 21 76 77.…”
Section: Resultsmentioning
confidence: 97%
“…In the univariate regression analysis, WHR was the only positive predictor of higher CIMT Z-score, while systolic and diastolic blood pressure showed a trend toward significance. In the SABPA study, Veldsman et al showed significant positive relationships between CIMT and WC in teachers undertaking light physical activity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that other factors that were not included in this study may have contributed to cIMT variance. Studies showed that the lifestyle factors such as alcohol consumption, dietary habits and physical activity, as well as job stress and cognitive performance, are associated with cIMT variance [ 34 , 35 , 36 ]. The early screening of cIMT and more aggressive management are warranted for patients with hypertension, especially if they are elderly, have central obesity and have high levels of glucose and lipid.…”
Section: Discussionmentioning
confidence: 99%